Red Sea studies: A historiographical sketch - Eivind Heldaas Seland (Polish Archaeology in the Mediterranean, 2020)
With the coming of age of Red Sea studies, William Facey’s description of “a sea on the way to somewhere else” has been demonstrated to be only one of the stories that can be told about the region. Starting as appendices to classical and orientalist scholarship, the archaeology and history of the Red Sea has over the last three decades emerged as a scholarly field in its own right. This paper discusses how scholars have approached the distant past of the region, highlighting some of the influences that have shaped Red Sea studies, and points to some of the challenges and opportunities that have been opened.